The taming of scarcity and the problems of plenty rethinking international relations and American grand strategy in a new era - Gavin, Francis J.; International Institute for Strategic Studies (Abingdon, Oxon New York, NY Routledge for the International Institute for Strategic Studies, 2024)
"The underlying structure, incentives and costs shaping international relations, state behaviour and the nature of power are profoundly different today to how they were in the past, in ways that are scarcely recognised and widely misunderstood. For much of history, world politics was marked by profound scarcity in resources, information and security. A series of historical revolutions has largely tamed this scarcity in ways few could have imagined. These revolutions, however, have generated new, potentially catastrophic challenges for the world--the problems of plenty. In this Adelphi book, Francis J. Gavin argues that the institutions, practices, theories and policies that helped explain and largely tamed scarcity by generating massive prosperity, and which were sometimes used to justify punishing conquest, are often unsuitable for addressing the problems of plenty. Successful grand strategy in this new age of abundance requires new thinking. New conceptual lenses, innovative policies and processes, and transformed institutions will be essential for confronting and solving the problems of plenty, without undermining the expanding efforts against scarcity."-- Publisher description.
War and conquest in the age of scarcity -- The taming of scarcity and the end of empire -- The problems of plenty -- Unspoken assumptions, time lags and historical anamnesis -- American grand strategy in a world of plenty.
Includes bibliographical references (pages 97-104).
Keywords: Scarcity; World politics -- 21st century; International relations -- History -- 21st century